Polymer electrolyte composition and preparation method and application thereof

Through the combination of 1,3-dioxolane and fluorovinyl carbonate, a polymer electrolyte with an interpenetrating network structure is formed, which solves the problems of insufficient fluidity and poor circulation performance of polymer electrolytes and improves the ionic conductivity of lithium batteries. Compatibility with interfaces, enhances flame retardant performance and self-repair capabilities, and significantly improves the battery's circulation and safety performance.

CN119297389AActive Publication Date: 2025-01-10JINLONGYU NEW ENERGY (SHENZHEN) CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411369039.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-09-24
Filing Date
2024-09-29
Publication Date
2025-01-10
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

Polymer electrolytes cannot flow like liquid electrolytes and are difficult to penetrate into the internal pores of porous electrodes, resulting in a decrease in the utilization rate and energy density of active materials, and their circulation performance is poor.

Method used

Using the combination of 1,3-dioxolane and fluorovinyl carbonate, the in-situ ring-opening polymerization under heat-induced conditions to form a polymerized electrolyte with an interpenetrating network structure, which improves ionic conductivity and interface compatibility and inhibits lithium branches. Crystal growth enhances flame retardant performance and automatically repairs after external force damage.

Benefits of technology

Significantly improve the circulation and safety performance of lithium batteries, improve the ionic conductivity and interface compatibility of the battery, increase the electrochemical window, reduce gas production during the cycle, and ensure the circulation and safety performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297389A_ABST
    Figure CN119297389A_ABST
Patent Text Reader

Abstract

The invention relates to a polymer electrolyte composition and a preparation method and application thereof, and belongs to the technical field of methods or devices for directly converting chemical energy into electric energy. The polymer electrolyte composition comprises a polymeric monomer, an initiator I, an initiator II and a lithium salt, the polymeric monomer is composed of 1, 3-dioxolame and fluoroethylene carbonate; the initiator I is an initiator of 1, 3-dioxolane, and the initiator II is an initiator of fluoroethylene carbonate. Polyelectrolyte formed by polymerizing the polymer electrolyte composition has good self-repairing performance and flame retardance, and a battery cell prepared from the polymer electrolyte has excellent cycle performance and high safety.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of methods or devices for directly converting chemical energy into electrical energy, and in particular to a polymer electrolyte composition and a preparation method and application thereof. Background Art

[0002] Compared with electrolytes, solid electrolytes have high mechanical strength, good electrochemical stability and thermal stability, and good compatibility with lithium metal negative electrodes or high-voltage positive electrodes, which can significantly improve the safety and energy density of lithium batteries. Solid electrolytes are mainly divided into inorganic electrolytes and polymer electrolytes, among which polymer electrolytes are mainly made into self-supporting membranes separately and then assembled in the battery. However, polymer electrolytes cannot flow like liquid electrolytes and are difficult to penetrate into the internal pores of porous electrodes, resulting in a decrease in the utilization rate of active materials and energy density.

[0003] To address this problem, people began to use an in-situ polymerization process to directly inject the liquid precursor solution of the polymer electrolyte into the battery, and then initiate in-situ polymerization under certain conditions to form a polymer electrolyte. Since the liquid precursor solution can maintain good fluidity, it can well infiltrate the electrode and form a closer interface contact after polymerization, thereby effectively improving the ionic conductivity of the battery. For example, the prior art (CN 113839096A) discloses a method for preparing a polymer electrolyte by in-situ polymerization, a lithium-ion battery and a preparation method thereof, wherein fluoroethylene carbonate and lithium salt are used as plasticizers and initiators, and are combined with monomers such as vinyl carbonate, methyl methacrylate, 1,3-dioxolane and trioxymethylene to form a polymer electrolyte by in-situ polymerization; although the ionic conductivity of the polymer electrolyte can reach 10 -3 S / cm level, but its cycle performance is poor. Summary of the invention

[0004] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a polymer electrolyte composition and a preparation method and application thereof.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] In the first aspect, the present invention provides a polymer electrolyte composition, comprising a polymer monomer, an initiator I, an initiator II and a lithium salt; the polymer monomer is composed of 1,3-dioxolane (CAS No. 646-06-0) and fluoroethylene carbonate (CAS No. 114435-02-8); the initiator I is an initiator of 1,3-dioxolane, and the initiator II is an initiator of fluoroethylene carbonate.

[0007] The present invention combines 1,3-dioxolane and fluoroethylene carbonate, and utilizes 1,3-dioxolane and fluoroethylene carbonate to form a polymer electrolyte with an interpenetrating network structure through in-situ ring-opening polymerization under thermal initiation conditions, which can not only improve the ionic conductivity and interface compatibility of the polymer electrolyte, but also inhibit the growth of lithium dendrites while enhancing the flame retardant performance, thereby significantly improving the cycle performance and safety performance of the battery. Moreover, the polymer electrolyte formed by polymerization has a certain fluidity and can automatically repair to the original state after being damaged by external force, thereby ensuring the cycle performance and safety performance of the battery.

[0008] In addition, the mass proportion of the polymerized monomer in the above-mentioned polymer electrolyte composition is preferably ≥60%, more preferably 65% ​​to 85%; specifically, it can be 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%.

[0009] Preferably, the mass fraction of 1,3-dioxolane in the polymerized monomer is ≤70%; optionally, the mass fraction of 1,3-dioxolane in the polymerized monomer can be 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%. Studies have found that when the mass fraction of 1,3-dioxolane in the polymerized monomer is ≤70%, not only can the formed polymer electrolyte maintain excellent cycle performance, but also can significantly increase its electrochemical window.

[0010] As a preferred embodiment of the polymer electrolyte composition of the present invention, the mass fraction of 1,3-dioxolane in the polymerized monomer is 30% to 50%. Optionally, the mass fraction of 1,3-dioxolane in the polymerized monomer can be 32%, 34%, 36%, 38%, 40%, 42%, 44%, 46%, 48%. Studies have found that when the mass fraction of 1,3-dioxolane in the polymerized monomer is 30% to 50%, it can not only better broaden the electrochemical window of the polymer electrolyte, but also significantly reduce the gas production during the battery cycle, thereby effectively improving the battery cycle performance.

[0011] As a preferred embodiment of the polymer electrolyte composition of the present invention, the initiator I comprises LiPF 6 、LiODFB、Mg(TFSI) 2 Mg(CF 3 SO 3 ) 2 , R-BF 3 -Li; said R-BF 3 R in -Li is an alkyl group.

[0012] As a preferred embodiment of the polymer electrolyte composition of the present invention, the initiator II includes at least one of stannous octoate, dibutyltin dilaurate, dibutyltin didodecylsulfide, dibutyltin diacetate, and tin tert-butoxide.

[0013] As a preferred embodiment of the polymer electrolyte composition of the present invention, the polymer electrolyte composition also includes a solvent, and the solvent includes at least one of methyl trifluoroethyl carbonate, methyl difluoroacetate, ethyl 2,2,2-trifluoroacetate, 3,3,3-trifluoropropylene carbonate, bis(2,2,2-trifluoroethyl) carbonate, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, ethyl methyl carbonate, diethyl carbonate, and dimethyl carbonate.

[0014] In a second aspect, the present invention provides a method for preparing the above-mentioned polymer electrolyte composition, comprising the following steps: mixing the components uniformly to obtain the polymer electrolyte composition.

[0015] Preferably, in the above preparation method, the components are mixed uniformly in a water-proof and oxygen-proof environment.

[0016] In a third aspect, the present invention provides use of the above polymer electrolyte composition in preparing an electrolyte by in-situ polymerization.

[0017] In a fourth aspect, the present invention provides a gel polymer electrolyte, which is obtained by polymerizing the above polymer electrolyte composition at 25-50°C for 5-48h (primary polymerization) and then polymerizing at 60-85°C for 48-96h (secondary polymerization). Optionally, the temperature of the above primary polymerization can be 30°C, 35°C, 40°C, 45°C, and the time can be 10h, 15h, 20h, 25h, 30h, 35h, 40h, 45h; the temperature of the secondary polymerization can be 65°C, 70°C, 75°C, 80°C, and the time can be 50h, 55h, 60h, 65h, 70h, 75h, 80h, 85h, 90h, 95h.

[0018] In a fifth aspect, the present invention provides a secondary battery, which includes a positive electrode plate, a negative electrode plate and an electrolyte, and the electrolyte is the above-mentioned gel polymer electrolyte.

[0019] In a sixth aspect, the present invention provides an electrical device, comprising the above-mentioned secondary battery, wherein the secondary battery serves as a power supply for the electrical device.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The present invention combines 1,3-dioxolane and fluoroethylene carbonate, and utilizes 1,3-dioxolane and fluoroethylene carbonate to form a polyelectrolyte with an interpenetrating network structure through in-situ ring-opening polymerization under thermal initiation conditions. The polyelectrolyte can not only improve the ionic conductivity and interface compatibility of the polymer electrolyte, but also inhibit the growth of lithium dendrites while enhancing the flame retardant performance, thereby significantly improving the cycle performance and safety performance of the lithium battery; moreover, the polymer electrolyte formed by polymerization has a certain fluidity and can automatically repair to the original state after being damaged by external force, thereby ensuring the cycle performance and safety performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The infrared spectra of 1,3-dioxolane, fluoroethylene carbonate and the polymer electrolyte prepared by using the polymer electrolyte composition in Example 1;

[0023] Figure 2 is an LSV curve diagram of a polymer electrolyte prepared using the polymer electrolyte composition in Comparative Example 1;

[0024] Figure 3 is an LSV curve diagram of a polymer electrolyte prepared using the polymer electrolyte composition in Example 1;

[0025] Figure 4 The cycle performance diagram of the in-situ polymer electrolyte lithium battery prepared using the polymer electrolyte composition in Example 1;

[0026] Figure 5 The following is a photograph of the self-healing test of the polymer electrolyte prepared using the polymer electrolyte composition in Example 3.

[0027] Figure 6 This is a photograph of the flame retardancy test of the polymer electrolyte prepared using the polymer electrolyte composition in Example 1. DETAILED DESCRIPTION

[0028] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0029] Unless otherwise specified, other materials, reagents, etc. used in the examples can be obtained from commercial sources.

[0030] Example 1

[0031] An embodiment of the polymer electrolyte composition of the present invention comprises the following components by weight: 6.592 parts of a polymer monomer (1,3-dioxolane + fluoroethylene carbonate, wherein the mass fraction of 1,3-dioxolane is 37.5%), 1.648 parts of a solvent (ethyl methyl carbonate, EMC), 0.44 parts of an initiator I (LiDFOB), 1.319 parts of a lithium salt (LiTFSI), 0.0412 parts of an initiator II (stannous octoate, Sn(Oct) 2 ).

[0032] The preparation method of the polymer electrolyte composition described in this embodiment is: in the absence of water and oxygen, the polymerization monomer, initiator I, initiator II, lithium salt and solvent are uniformly mixed to obtain the polymer electrolyte composition.

[0033] Example 2

[0034] An embodiment of the polymer electrolyte composition of the present invention is substantially the same as that of embodiment 1, except that the mass fraction of 1,3-dioxolane in the polymerized monomer is 40%.

[0035] The preparation method of the polymer electrolyte composition described in this embodiment is the same as that in Embodiment 1.

[0036] Example 3

[0037] An embodiment of the polymer electrolyte composition of the present invention is substantially the same as that of embodiment 1, except that the mass fraction of 1,3-dioxolane in the polymerized monomer is 50%.

[0038] The preparation method of the polymer electrolyte composition described in this embodiment is the same as that in Embodiment 1.

[0039] Example 4

[0040] An embodiment of the polymer electrolyte composition of the present invention is substantially the same as that of embodiment 1, except that the mass fraction of 1,3-dioxolane in the polymerized monomer is 70%.

[0041] The preparation method of the polymer electrolyte composition described in this embodiment is the same as that in Embodiment 1.

[0042] Example 5

[0043] An embodiment of the polymer electrolyte composition of the present invention comprises the following components by weight: 8.256 parts of a polymer monomer (1,3-dioxolane + fluoroethylene carbonate, wherein the mass fraction of 1,3-dioxolane is 50%), 0.427 parts of an initiator I (LiDFOB), 1.308 parts of a lithium salt (LiTFSI), 0.0412 parts of an initiator II (stannous octoate (Sn(Oct) 2 )).

[0044] The preparation method of the polymer electrolyte composition described in this embodiment is the same as that in Embodiment 1.

[0045] Example 6

[0046] An embodiment of the polymer electrolyte composition of the present invention comprises the following components by weight: 8.026 parts of a polymer monomer (composed of 1,3-dioxolane and fluoroethylene carbonate, wherein the mass fraction of 1,3-dioxolane is 50%), 0.231 parts of an initiator I (LiPF 6 )、1.744 parts of lithium salt (LiTFSI), 0.0401 parts of initiator II (stannous octoate (Sn(Oct) 2 )).

[0047] The preparation method of the polymer electrolyte composition described in this embodiment is the same as that in Embodiment 1.

[0048] Comparative Example 1

[0049] A comparative example of the polymer electrolyte composition of the present invention is substantially the same as Example 1, except that the polymerizable monomer is 1,3-dioxolane.

[0050] The preparation method of the polymer electrolyte composition in this comparative example is the same as that in Example 1.

[0051] Comparative Example 2

[0052] A comparative example of the polymer electrolyte composition of the present invention is substantially the same as Example 1, except that the polymerizable monomer is fluoroethylene carbonate.

[0053] The preparation method of the polymer electrolyte composition in this comparative example is the same as that in Example 1.

[0054] Comparative Example 3

[0055] A comparative example of the polymer electrolyte composition of the present invention is substantially the same as Example 1, except that it does not contain initiator II (ie, fluoroethylene carbonate cannot be ring-opening polymerized).

[0056] The preparation method of the polymer electrolyte composition in this comparative example is the same as that in Example 1.

[0057] Comparative Example 4

[0058] A comparative example of the polymer electrolyte composition of the present invention is basically the same as Example 1, except that: the polymerized monomer consists of 1,3-dioxolane and vinyl ethylene carbonate, wherein the mass fraction of 1,3-dioxolane is 37.5%; and the initiator II is azobisisobutyronitrile.

[0059] The preparation method of the polymer electrolyte composition in this comparative example is the same as that in Example 1.

[0060] Performance Testing

[0061] 1. Infrared spectrum test

[0062] The polymer electrolyte composition in Example 1 was polymerized at 45°C for 24 hours, and then heated to 80°C for further polymerization for 72 hours to obtain a polymer electrolyte. The polymer electrolyte was tested by Fourier transform infrared spectroscopy. The test results are as follows: Figure 1 As shown. Figure 1 It can be seen that 1,3-dioxolane is located at 1000-1200cm -1 The characteristic peak at 1800 cm-1 disappeared after the copolymerization of 1,3-dioxolane and fluoroethylene carbonate, while the characteristic peak of fluoroethylene carbonate at 1800 cm-1 -1 The characteristic peak at 1,3-dioxolane and fluoroethylene carbonate is significantly reduced after copolymerization, indicating that 1,3-dioxolane undergoes ring-opening polymerization to form poly-1,3-dioxolane and fluoroethylene carbonate undergoes ring-opening polymerization to form polyfluoroethylene carbonate, which proves that the polymer electrolyte composition of the present invention can be in-situ polymerized to form a polymer electrolyte under the action of thermal initiation.

[0063] 2. Electrochemical window test

[0064] The test method is: respectively assemble the polymer electrolyte composition in Comparative Example 1 and Example 1 together with the diaphragm into a steel sheet / diaphragm (PP diaphragm with a thickness of 12 μm) + polymer electrolyte composition / steel sheet blocked battery, place it at 45°C for in-situ polymerization for 24 hours, then heat it to 80°C and continue in-situ polymerization for 72 hours, and then use an electrochemical workstation to test the LSV curve, the test voltage range is 3 to 5 V, and the voltage step is 1 mV / s.

[0065] Test results such as Figure 2 and Figure 3 As shown, according to Figure 2It can be seen that when the polymerized monomer in the polymer electrolyte composition is 1,3-dioxolane, the electrochemical window of the electrolyte formed by in situ polymerization is only 4.1V; and when the polymerized monomer in the polymer electrolyte composition is a mixture of 1,3-dioxolane and fluoroethylene carbonate, the electrochemical window of the electrolyte formed by in situ polymerization is greater than 4.4V, which indicates that the combination of 1,3-dioxolane and fluoroethylene carbonate can effectively improve the electrochemical window of the polymer electrolyte.

[0066] 3. Cycle performance test

[0067] The polymer electrolyte composition in each embodiment and comparative example is prepared into an in-situ polymer electrolyte lithium battery, and the preparation method comprises the following steps:

[0068] A positive electrode plate, a separator (PP separator with a thickness of 12 μm) and a negative electrode plate are stacked to form a dry battery cell. After the battery cell is baked, 10 g (10 Ah battery cell) of the polymer electrolyte composition in each embodiment and comparative example is injected into the dry battery cell under the condition of anhydrous and oxygen-isolated conditions, and left to stand for 24 hours; then the battery cell is placed at 45° C. for in-situ polymerization for 24 hours, and then the temperature is raised to 80° C. for further in-situ polymerization for 72 hours to obtain an in-situ polymerized electrolyte lithium battery;

[0069] The negative electrode plate in the above preparation method is a lithium-copper composite strip (a lithium metal layer is pressed on the copper surface); the positive electrode plate is composed of aluminum foil and a positive electrode material coated on the aluminum foil, and the positive electrode material is composed of commercial high-nickel ternary (NCM811), polyvinylidene fluoride (PVDF) and single-walled carbon nanotubes in a mass ratio of 9:0.5:0.5.

[0070] The above-mentioned in-situ polymerized electrolyte lithium battery was subjected to a cycle performance test, and was charged and discharged for 100 cycles at 0.33C in the range of 2.5 to 4.2V at 25°C.

[0071] First cycle efficiency (%) = discharge specific capacity of the first cycle / charge specific capacity of the first cycle × 100%;

[0072] Capacity retention rate (%) = 100th cycle discharge specific capacity / 1st cycle discharge specific capacity × 100%. Table 1 First cycle capacity, first cycle efficiency and capacity retention rate of in-situ polymer electrolyte lithium batteries prepared using polymer battery compositions of various embodiments and comparative examples

[0073]

[0074] According to the data in Table 1 and Figure 4It can be seen that the first cycle capacity and first cycle efficiency of the polymer electrolyte formed by in-situ polymerization of the polymer electrolyte composition in Examples 1 to 6 reach 5Ah and 87% or more, respectively, and the capacity retention rate after 100 cycles is greater than or equal to 92.78%, indicating that the polymer electrolyte prepared by in-situ polymerization of the polymer electrolyte composition of the present invention can not only give the battery a good first cycle capacity and first cycle efficiency, but also significantly improve its cycle performance. At the same time, according to Comparative Examples 1 and 2, it can be seen that the polymer electrolyte formed by in-situ polymerization with 1,3-dioxolane or fluoroethylene carbonate as a polymerization monomer alone is difficult to effectively improve the cycle performance of the battery; according to Comparative Example 3, it can be found that fluoroethylene carbonate is used as an additive and acts together with poly 1,3-dioxolane to improve the cycle performance of the battery to a certain extent, but the degree of improvement is limited; according to Comparative Example 4, it can be found that when fluoroethylene carbonate is replaced with ethylene carbonate and used together with 1,3-dioxolane as a polymerization monomer, the polymer electrolyte formed by in-situ polymerization is not only difficult to improve the first cycle capacity and first cycle efficiency of the battery, but also cannot effectively improve the cycle performance of the battery.

[0075] 4. Self-healing performance test

[0076] The polymer electrolyte composition in Example 3 was first polymerized at 45°C for 24 hours, and then heated to 80°C for 72 hours to form a polymer electrolyte; then two portions of the polymer electrolyte were placed on the surface of weighing paper and separated by a certain distance (such as Figure 5 After standing for 30 minutes, the two polymer electrolytes were found to be completely fused together (as shown in A). Figure 5 B), indicating that the polymer solid electrolyte formed after the polymer electrolyte composition of the present invention is cured has a certain fluidity and can achieve self-repair; the polymer electrolytes polymerized from the polymer electrolyte compositions in Examples 1 to 2 and Examples 4 to 6 are similar to Example 3 and have good self-repair performance.

[0077] 5. Flame retardant performance test

[0078] The polymer electrolyte composition in Example 1 was first polymerized at 45°C for 24 hours, then heated to 80°C and continued to polymerize for 72 hours to form a polymer electrolyte, which was then placed in an external flame of an electronic lighter and burned for 2 to 3 seconds (e.g. Figure 6 After the burning stops, the polymer electrolyte immediately extinguishes itself (as shown in Figure 6 B), indicating that the polymer electrolyte has good flame retardant properties; the polymer electrolytes polymerized from the polymer electrolyte compositions in Examples 2 to 6 are similar to those in Example 1, and all have good flame retardant properties.

[0079] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A polymer electrolyte composition, characterized in that The invention comprises a polymerizable monomer, an initiator I, an initiator II and a lithium salt; the polymerizable monomer is composed of 1,3-dioxolane and fluoroethylene carbonate; the initiator I is an initiator of 1,3-dioxolane, and the initiator II is an initiator of fluoroethylene carbonate.

2. The polymer electrolyte composition according to claim 1, characterized in that The mass fraction of 1,3-dioxolane in the polymerization monomer is 30% to 50%.

3. The polymer electrolyte composition according to claim 1, characterized in that The initiator I includes at least one of LiPF6, LiODFB, Mg(TFSI)2, Mg(CF3SO3)2, and R-BF3-Li; R in the R-BF3-Li is an alkyl group.

4. The polymer electrolyte composition according to claim 1, characterized in that The initiator II includes at least one of stannous octoate, dibutyltin dilaurate, dibutyltin didodecylsulfide, dibutyltin diacetate, and tin tert-butoxide.

5. The polymer electrolyte composition according to claim 1, characterized in that The polymer electrolyte composition also includes a solvent, which includes at least one of methyl trifluoroethyl carbonate, methyl difluoroacetate, ethyl 2,2,2-trifluoroacetate, 3,3,3-trifluoropropylene carbonate, bis(2,2,2-trifluoroethyl) carbonate, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, ethyl methyl carbonate, diethyl carbonate, and dimethyl carbonate.

6. The method for preparing the polymer electrolyte composition according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: mixing the components uniformly to obtain a polymer electrolyte composition.

7. Use of the polymer electrolyte composition according to any one of claims 1 to 5 in preparing electrolytes by in-situ polymerization.

8. A gel polymer electrolyte, characterized in that: The polymer electrolyte composition according to any one of claims 1 to 5 is first polymerized at 25 to 50° C. for 5 to 48 hours and then polymerized at 60 to 85° C. for 48 to 96 hours to obtain the polymer electrolyte composition.

9. A secondary battery comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, characterized in that: The electrolyte is the gel polymer electrolyte according to claim 8.

10. An electrical device, characterized in that: The secondary battery according to claim 9 is included, and the secondary battery is used as a power supply for the electrical device.

Citation Information

Patent Citations

  • High-voltage-resistant solid polymer electrolyte, and preparation method and application thereof

    CN109671978A

  • Method for preparing polymer electrolyte through in-situ polymerization, lithium ion battery and preparation method of lithium ion battery

    CN113839096A

  • Polymer composite solid electrolyte and preparation method and application thereof

    CN118380647A